EFEK VARIASI DAYA IRADIASI GELOMBANG MIKRO TERHADAP KARBON AKTIF TONGKOL JAGUNG UNTUK PENJERNIHAN AIR - Raysa Fadillah; Rakhmawati Farma; Awitdrus Awitdrus (Komunikasi Fisika Indonesia, 2018)
The power of microwave irradiation affect the quality of activated carbon. In this research the activated carbon has been made of biomass of corn cob by using carbonization process, chemical activation using potassium hydroxide as the activating agent and microwave irradiation power was variated for 360 watt, 450 watt, 630 watt, dan 720 watt in 15 minutes. The surface morphology of activated carbon for the sample KA720 produced lots of pores more than that of the sample KA360, KA450, and KA630. The sea water that has been mixed with activaed carbon using microwave irradiation power of 720 watt with temperatur of 26oC, and pH of 7,41.